It isn’t over ‘till it’s over: A continuing concern of the SARS-CoV-2 variants, and miRNAs targeting the S protein as a probable absolute cure - Kilic, Pelin; Cosar, Begüm; Ince, Ahmet Turan; Cebbaroglu, Doruk Deniz; Tekeli, Cansu; Benli, Esma; Darcansoy Iseri, Ozlem (EXPERIMENTAL BIOMEDICAL RESEARCH, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak which still continues to affect the general population, has mutated day by day and new variants have emerged. More than 40 variants, usually caused by mutations in the spike (S) protein, have been recorded. Observation of S protein mutations in the development of t herapeutic agents will increase success rates. As we identify the three-dimensional (3D) conformation of viruses, it is more and more possible to work on models for understanding molecular interactions. Development of agents for arrays and 3D sequencing of proteins paves the way for potential therapeutic studies against variants. MicroRNAs (miRNAs) seemingly act as a potentially important group of biomolecules in combating uncontrolled cytokine release. Besides antiviral response, miRNAs promise to be powerful therapeutic agents against infections. Studies have shown that miRNAs are able to inhibit the genome directly by miRNA-based treatments as they are sprecific to the SARS-CoV-2 genome. In order to expose this potential, in silico studies before continuing with lab studies are helpful. In our bioinformatics analysis, we proposed to compare the S protein similarities of Delta and Omicron, two of the most common variants, and to detect miRNAs targeting the S protein. The S proteins and coding sequences were compared between the two variants, and differences were determined. Within our analysis, 105 and 109 miRNAs for the Delta and Omicron variants, respectively, were detected. We believe that our study will be a potential guide for deciding on the miRNAs that may most likely have an effect on the management of the infection caused by both variants.